IMPLEMENTATION OF THE PRINCIPLE OF AGREEMENT ON THE AGREEMENT ON THE BINDING OF SALE AND PURCHASE OF LAND RIGHTS IN THE NOTARY / PPAT DISTRICT OF RUMBAI, PEKANBARU CITY. - Yeni Triana; Cenuk Widiastrisna Sayekti; Cicilia Mayori (Prosiding Seminar Nasional Pakar, 2020)
The purpose of this study is to analyze the principle of agreement in the binding agreement of the sale and purchase of land rights, prior to the issuance of the sale and purchase deed by the Notary. So that what has been agreed upon by both parties can be realized in the sale and purchase deed, so that there will be a transfer of land rights. The target to be achieved in this research activity is to increase understanding for both parties, both the seller and the buyer, and even the general public. Regarding the principle of agreement on the binding agreement of sale and purchase of land rights, as well as for the researchers themselves making a very important contribution to the legal problems faced by the community, especially regarding the binding agreement on the sale and purchase of land rights, and the legal consequences of the agreement. The research method is by sociological law, the location of the study is the community and the Notary Office located in Rumbai District, Pekanbaru City, the population and the sample are the land sellers, buyers, Notaries, with oral interview method in order to find information as data processed in this study. The output produced according to the activity plan for the proposer is in the form of scientific articles, and learning study materials for students.